Legal Aspects of Social Transformation in Lgbt Community: Exploring the Legal Aspects of Social Transformation in the LGBT Community (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Transgender, Intersex, Homosexual, Gay , Bisexual, Kinnar, Hijra, and Queer categories include LGBT. The current Article aims to investigate the social transition or social transformation of LGBT in respect of its legal aspects. After insight study on the related topics I, as a researcher found that it is not possible to conclude anything on the issues related to this community and the study of theorical aspects of published and unpublished material is required and it is must to do the justice too.Since time immemorial, all these people who constitute a minority and are homosexuals are not welcome. They are not regarded as human beings. If homosexual or gay people remain together, they are deemed against the law. Since time immemorial these people face social inequality in society. In 1862 the British parliament passed a law banning such actions for the good of society. This LGBT group of people has been battling the discrimination and they have always been rejected by a family and society worldwide. The LGBT community began battling this injustice done to them in 2014 and eventually, this unnatural conduct was decriminalised under Section 377 on 6th September 2018. This minority got a sign of relief after the verdict, but not relieved. At least, they can live a life where they don't have to fear the police. With integrity, they will face life and they can get work. It can be assumed that after the judgement of 6th September 2018 which decriminalises it, there has been a social change in their life. While not entirely relaxed, minority has shown a sign of relief.